Role Of Nidra In Relieving Mental Health - Parihar, Sangeeta; Sarika Yadav; Mourya, Meenakshi (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Nidra, one of the three essential pillars (Trayopstambha) of life according to Ayurveda, plays a vital role in sustaining health and well-being. It is as crucial as Ahara and Brahmacharya. This study explores the physiological processes of sleep and its profound impact on mental well-being. Proper sleep is necessary for the maintenance of homeostasis, mental clarity, emotional balance, and physical health. In this study, the physiological mechanisms of sleep and its impact on mental health from an Ayurvedic perspective. Material and Methods: A thorough review of classical Ayurvedic texts, to understand Nidra and its impact on mental health. Additionally, academic journals and articles were referenced, and databases like Google Scholar, Research Gate, and PubMed Central were extensively searched for relevant review articles. Discussion- Nidra (sleep) is a foundational element in Ayurveda, vital for homeostasis, emotional balance, and overall health. The teachings of Acharya Charaka and Sushruta emphasize the role of sleep role in preventing and managing mental and physical disorders. Acharya Sushruta explains that Tamas and Shleshma influence the heart and mind, inducing Nidra, similar to how neurotransmitters and circadian rhythms regulate sleep in modern physiology. In contrast, Nidranasha (lack of sleep) can lead to mental disturbances, stress, anxiety, and other psychological issues, underscoring the critical role of sleep in both ancient and modern contexts. Conclusion: In Ayurveda, Nidra (sleep) is vital for physical restoration and mental balance, playing a crucial role in managing stress, anxiety, and overall health.